Stress granules: potential therapeutic targets for infectious and inflammatory diseases - Li, Wenyuan; Wang, Yao (Frontiers in Immunology, 2023)
Eukaryotic cells are stimulated by external pressure such as that derived from heat shock, oxidative stress, nutrient deficiencies, or infections, which induce the formation of stress granules (SGs) that facilitates cellular adaptation to environmental pressures. As aggregated products of the translation initiation complex in the cytoplasm, SGs play important roles in cell gene expression and homeostasis. Infection induces SG formation. Specifically, a pathogen that invades a host cell leverages the host cell translation machinery to complete the pathogen life cycle. In response, the host cell suspends translation, which leads to SG formation, to resist pathogen invasion. This article reviews the production and function of SGs, the interaction between SGs and pathogens, and the relationship between SGs and pathogen-induced innate immunity to provide directions for further research into anti-infection and anti-inflammatory disease strategies.